Lecturers' psychological well-being: Impact of leadership style on work climate, self-compassion, and gratitude - Ema Yudiani; Listya Istiningtyas; Jesyia Meyrinda; Siti Khosiyah (Social Sciences and Humanities Open, 2025)
Psychological well-being (PWB) is critical in human resource management, as lower PWB can negatively impact lecturers' effectiveness and performance. This study surveyed 645 lecturers across various Indonesian provinces to assess work climate, self-compassion, gratitude, leadership style, and PWB. Data collection was conducted using a structured online questionnaire, and the data were analyzed using structural equation modelling (SEM) to evaluate the structural model and regression weights, explicitly examining the moderating effect of transformational leadership. The findings indicate that transformational leadership significantly enhances the effects of work climate and self-compassion on PWB. However, it has a limited moderating effect on the relationship between gratitude and PWB. This suggests that leadership style is crucial in how work climate and self-compassion contribute to PWB.This study contributes to the existing literature by applying the Job Demands-Resources (JD-R) theory within the context of Indonesian State Islamic Religious Colleges. The novelty of this research lies in examining transformational leadership as a moderator in this unique educational setting. The findings highlight the importance of fostering transformational leadership styles within institutions to promote a supportive work environment and enhance lecturer well-being, which may improve overall performance and educational outcomes.